EPOP and MTF2 activate PRC2 activity through DNA-sequence specificity - Jeffrey Granat; Sanxiong Liu; Luis Popoca; Ozgur Oksuz; Danny Reinberg (Proceedings of the National Academy of Sciences, 2026)
Polycomb Repressive Complex 2 (PRC2) facilitates the formation of facultative heterochromatin, instrumental to tissue specific gene expression. PRC2 catalyzes trimethylation of lysine 27 of histone H3 (H3K27me3), which is targeted for chromatin compaction by PRC1. Importantly, PRC2-associated cofactors regulate its distinct activities, as in the case of MTF2 and JARID2 that direct PRC2 to specific chromatin nucleation sites based on preferred DNA-binding motifs. Here, we investigated EPOP whose role in regulating PRC2 was not well-defined. We find that both EPOP and MTF2 stimulate PRC2 histone methyltransferase (HMT) activity in vitro. Unlike MTF2, EPOP is ineffectual in PRC2 chromatin recruitment as evidenced by an EED-rescue system in vivo but promotes H3K27me3 deposition de novo in cooperation with MTF2 and JARID2. Binding assays using reconstituted dinucleosome substrates revealed that similar to MTF2, EPOP promotes PRC2 chromatin-binding activity in a distinct DNA-sequence-dependent manner (GCN-rich and GA-rich, respectively). Thus, EPOP and MTF2 in conjunction with JARID2 foster PRC2-mediated HMT activity at chromatin sites comprising cofactor-preferred DNA-binding sequences during the formation of H3K27me3-chromatin domains.